Raising the bar (19). Issue 1 (2nd January 2022) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Bond-Smith, Steven; Chasco, Coro; Corrado, Luisa; Ditzen, Jan; Felsenstein, Daniel; Fuerst, Franz; McCann, Philip; Monastiriotis, Vassilis; et al.
ABSTRACT: This editorial summarizes the papers published in issue 17(1) (2022). This issue begins with a second editorial calling on researchers to publish replication results from previous studies. The first paper applies a spatiotemporal Bayesian hierarchical model for understanding the dynamics of second home ownership in Corsica. The second paper determines the optimal time to invest in a new airport using real options analysis. The third paper employs unit root tests to provide empirical evidence that environmental policy changes have not been effective up to now. The fourth paper provides empirical evidence that regional spillover effects should play a crucial role in the policy discussion about climate change. The fifth paper forecasts the direct impact of climate change on crop yields in the agricultural sector and the indirect impacts on other sectors of the Brazilian economy up to 2100. The sixth paper investigates whether the percentage of women in national parliaments positively affects public expenditures on social needs both internally and in neighbouring countries. The seventh paper sets out a general framework for store sales evaluation and prediction.